UJI POTENSI ANTIFUNGI AKTINOMISETES SELULOLITIK DAN LIGNINOLITIK DAN BAKTERI LIGNOSELULOLITIK ISOLAT LOKAL TERHADAP PERTUMBUHAN JAMUR Ganoderma boninense DAN Colletotrichum capsici - Dede Martin; Atria Martina; Rodesia Mustika Roza (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Colletotrichum capsici fungi, causing agent of anthracnose in chili, and Ganoderma boninense, fungi causing agent of basal stem rotten in oil palm, can reduce the productivity of chili and oil palm. These disease are increasing so that it is necessary to find local biological agents that are environmentally friendly. The purpose of this research was to determine the potential isolates of lignocellulolyltic bacteria and cellulolytic and ligninolytic actinomycetes from peat soil of Rimbo Panjang Kampar, Riau as an antifungal agent to inhibit the growth of C. capsici and G. boninense.Antifungal activity was screened using agar disc method by measured the inhibition zone for seven days. The results showed that 13 isolates of actinomycetes haveantifungal activity against C. capsici with the highest inhibition zone 13,3 mm by RB2S40. Six isolates of actinomycetes have antifungal activity against G. boninense with the highest inhibition zone 29,15 mm by RB1S4. Five isolates have the ability to inhibit both fungi which were targeted.